ASSOCIATION BETWEEN NEUTROPHIL-TO-LYMPHOCYTE RATIO AND PLATELET-TO-LYMPHOCYTE RATIO WITH 1-YEAR MORTALITY IN HEMODIALYSIS PATIENT IN WANGAYA REGIONAL GENERAL HOSPITAL - I PUTU YOGI SASTRAWAN; CHRISTINA PERMATA SHALIM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this study was to determine whether neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are associated with mortality risk in patients with hemodialysis (HD). Methods: We conducted a retrospective cohort study among regular HD patients at Wangaya Regional General Hospital. Data were collected from patients’ medical records in June 2018 and followed up until May 2019. Results: NLR and PLR were significantly associated with 1-year mortality (p=0.047 and p=0.009), with higher NLR (NLR>2.84) and higher PLR (PLR>10) associated with higher risk of 1-year mortality (relative risk [RR]=3.36 and RR=5.19). Conclusion: NLR and PLR were significantly associated with 1-year mortality in patients with HD.